Medical Students’ Performance in Anatomy: Integrated Versus Subject-Based Scores - Islam, Sobia; Musarrat Khan, Huma; Rashid, Nadia; Akhtar, Lubna; Rashid, Sadia; Anwar, Noreen (Life and Science, 2023)
Objective: The objective of the study was to compare the Anatomy scores with Total scores in exams with Integrated results and exams with Subject-based results and to compare the Anatomy scores in exams with Integrated results with exams with Subject-based results.Study Design: Quantitative/observational, retrospective study, with Universal sampling.Place and Duration of Study: The study was conducted in the Department of Anatomy of Foundation University School of Health Sciences Islamabad, Pakistan, from 1st May 2022 to 31st August 2022.Materials and Methods: The study was conducted on scores of the First professional examination in two groups of MBBS students; Group A (n=150). The result was based on integrated scores, and Group B (n=149): Result was based on subject score. The mean Anatomy score (AS) percentage in Groups A & B was compared with the mean total score (TS) percentage in both groups, respectively, and with each other using Student’s t test.Results: The Anatomy score in Group A (63.72%±12.20) and Group B (66.26%±12.7) was less than the Total score (Group A:69.38%±8.79, Group B:67.56±10.93). This difference was statistically significant (p=0.00) in Group A. The Anatomy score in Group A was less than in Group B, but the difference was not statistically significant (p=0.08).Conclusion: The Anatomy score was significantly less than the Total score in exams with integrated results. Moreover, the Anatomy score was less in the exams with integrated results as compared to exams with subject-based Results.